Socialization of Waste Management in The Village Babakan Raden, Cariu, Bogor - Yuaniko Paramitra; Putri Vini Pratiwi; Qonitah Putri Purworini; Rachel Septiana Damanik (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this study was to find out how to manage waste in the Babakanraden Village area, the activities we carry out are community service to increase awareness, participation or participation of the Babakanraden Village community in good and correct waste management, and also know the role of the local government in realizing the village environmentally friendly. When the amount of waste increases, it will cause problems that can be harmful to humans, both health and the environment. Therefore, it is important to involve the village government as the government closest in position to the people. This research method uses empirical research methods with a statutory approach, to obtain data, researchers conduct observations and interviews with residents of Babakanraden Village and also the village government. The results of the observations that have been made reveal that there is still a lack of participation and a lack of community knowledge in waste management, as well as the role of the regional government which has not been maximized and covers all village areas. The village community still lacks a garbage collection area, and the habit of the village community is that they still throw garbage in any place.